A paired comparison of scat‐collecting versus scat‐swabbing methods for noninvasive recovery of mesocarnivore DNA from an arid environment. (8th November 2015) - Miles, Kathleen A.; Holtz, Michelle N.; Lounsberry, Zachary T.; Sacks, Benjamin N.
ABSTRACT: Noninvasive DNA sampling from scats can provide powerful tools for wildlife research depending in large part on how scats are collected in the field. Preservation of scat in 95–100% ethanol can be highly effective, but not always practical. Use of swabs to sample the mucous layer from scats is a popular alternative, but has not been adequately tested in arid environments, where the mucous layer can rapidly desiccate. We conducted a paired comparison of methods, extraction from scats stored in ethanol ("direct method") versus from swabs ("swab method"), for carnivore scats collected under typical field conditions during May–September 2013 and January–February 2015 in northern California, USA. Direct quantification of DNA indicated that the extracts from ethanol‐preserved direct‐method samples contained, on average, an order of magnitude (14×) more target DNA than extracts from swab method ( P  < 0.03). For mitochondrial sequencing, which is typically used for species‐typing, we obtained slightly higher success for the direct (81%) than the swab (73%) extracts, but not significantly so ( P  = 0.25, n  = 104). Among 62 canid scats, microsatellite genotyping (typically used for individual identification) was much more successful for the direct extracts (74%) than the swab extracts (35%; P  < 0.001, n  = 62). Together, our findings indicated a substantial advantage of ethanol preservation followed by extraction directly from scats over swabbing in our arid study area. Our results apply most specifically to canids in the arid study environment; swabbing is potentially more effective in humid environments or in other carnivore species. Nevertheless, our findings highlight the importance of conducting pilot studies before committing to swabbing as a means of fecal DNA collection. © 2015 The Wildlife Society.